Knowledge Management Approach in Law Enforcement Division of Indonesian Food and Drug Authority to Improve Organizational Performance - Terry Yessi Evelin; Dedy Sushandoyo; Emilia Fitriana Dewi (AIBPM Publisher, 2021)
Indonesian Food and Drug Authority (BPOM) functions are to conduct investigations into violations of Food and Drug Administration regulation. It protects the public from the illegal distribution of drugs, traditional medicines, dietary supplements, cosmetics, and foods that could harm health. However, in practice, the implementation of law enforcement has not been optimal due to several factors, including the lack of a system or database that allows for the sharing of knowledge, experience, and lessons learned that can aid in decision making regarding the law enforcement process. This research aims to assess the current system of knowledge management and find the knowledge management strategies that support the organization's performance. The findings show that the BPOM Law Enforcement Division currently lacks knowledge management. It shows that there is a lack of skill in converting tacit knowledge into explicit knowledge. The system does not support facilitation. Recommendations are made for the BPOM Law Enforcement Division to establish a standardized documentation and database system and build facilities, infrastructure, and information systems supported by the leader and system. This study can help all work units, particularly the Law Enforcement Division, improve quality and maximize available human resources.